Nilai-Nilai Dasar Moderasi dan Toleransi Beragama dalam Praktik Pengajaran di Pondok Pesantren Roudlotus Sholihin Demak - Muhammad Aslambik (2022)
Roudlotus Sholihin Islamic Boarding School is a boarding school located on Jl. Kyai Noer RT. 02 RW. 01 Loireng Sayung Kab. Demak. The uniqueness of this Islamic boarding school is that it teaches the values ​​of tolerance to its students since they are still at the junior high school level (Junior High School). What is unique is that at the Roudlotus Sholihin Islamic Boarding School it is not only in the form of theory without any practice, but at the Roudlotus Sholihin Islamic Boarding School the practice of moderation and tolerance education is also applied in the form of visiting various other places of worship to create intimacy and harmony between religious communities. Even in 2019, the Roudlotus Sholihin Islamic Boarding School sent its tambourine team to be displayed at the Mater Dei Catholic Church in Semarang. In this scientific paper, the author will explain the values ​​of religious moderation which are the basis for the practice of religious moderation in the Roudlotus Sholihin Islamic Boarding School. The author uses Literature Studies to strengthen the narrative in this scientific paper. The results of this study explain that the Prophet Muhammad as the best role model for mankind, especially for Muslims, exemplifies the values ​​of teaching, education, and the practice of moderation and tolerance for his people. This paper describes many examples of moderation and tolerance from the Prophet Muhammad as the basis for the application of education, teaching, and the practice of living in a harmonious and tolerant society in diversity.